Karl Mannheim and the legacy of Max Weber [ retrieving a research programme - Kettler, David , 1981; Loader, Colin , 1941-; Meja, Volker (Aldershot, England ;Burlington, VT : Ashgate, 2008)
Focuses on the work of Karl Mannheim by demonstrating how his theoretical conception of a reflexive sociology took shape as a collaborative empirical research program. This book shows how contemporary
1. The challenging context -- 2. Time and place -- 3. The social structure of advancement : education for life in the economy -- 4. The intensive study group around Karl Mannheim -- 5. Norbert Elias and the sociology of external forms -- 6. Hans Gerth and Hans Weil : the genealogy of the liberal bildungselite -- 7. Kathe Truhel and the idea of a social bureaucracy -- 8. Natalie Halperin and Margarete Freudenthal : the genealogy of women's movements -- 9. Jacob Katz : the sociology of the stranger I -- 10. Nina Rubinstein : sociology of the stranger II -- 11. Individual projects and orphans -- 12. The unfinished business between Karl Mannheim and Max Weber
Includes bibliographical references (p [197]-206) and index
Keywords: Mannheim, Karl , -- 1893-1947; Marx, Karl , -- 1818-1883; Knowledge, Sociology of; Knowledge, Sociology of; Mannheim, Karl